Cross-Cultural Adaptation and Analysis of the Psychometric Properties of the Portuguese Version of the Edinburgh Feeding Evaluation in Dementia Scale - Lígia Passos; João Tavares; Daniela Figueiredo (Karger Publishers, 2021)
Introduction: In advanced stages, people with dementia (PwD) may develop feeding difficulties. The assessment of these difficulties is the first step towards an adequate intervention. The Edinburgh Feeding Evaluation in Dementia Scale (EdFED) is an instrument for assessing the feeding difficulties of older PwD. Objective: The objective of this observational, cross-sectional, exploratory-descriptive study was to contribute to the adaptation of the EdFED to the Portuguese population and to analyze some of its psychometric properties, namely internal consistency and interobserver reliability. Methods: First, translation, cultural and linguistic adaptation, as well as validation were performed using an expert panel and calculation of the content validity index (CVI). Then the instrument was applied in 51 institutionalized older PwD (mean age 86.06 ± 6.77 years, 86.2% women). Results: The results showed excellent content validity, with a CVI of 0.950. The Portuguese version of the EdFED showed reasonable internal consistency (Cronbach's α = 0.705) and very satisfactory interobserver reliability (Cohen's κ = 0.882). Conclusion: The main results suggest that the Portuguese version of the EdFED is a reliable instrument that allows the assessment of eating/feeding difficulties among institutionalized older PwD.